The EyeHarp: A Gaze-Controlled Digital Musical Instrument - Vamvakousis, Zacharias; Ramirez, Rafael (Frontiers in Psychology, 2016)
We present and evaluate the EyeHarp, a new gaze-controlled Digital Musical Instrument, which aims to enable people with severe motor disabilities to learn, perform, and compose music using only their gaze as control mechanism. It consists of (1) a step-sequencer layer, which serves for constructing chords/arpeggios, and (2) a melody layer, for playing melodies and changing the chords/arpeggios. We have conducted a pilot evaluation of the EyeHarp involving 39 participants with no disabilities from both a performer and an audience perspective. In the first case, 8 people with normal vision and no motor disability participated in a music-playing session in which both quantitative and qualitative data were collected. In the second case 31 people qualitatively evaluated the EyeHarp in a concert setting consisting of two parts: a solo performance part, and an ensemble (EyeHarp, two guitars and flute) performance part. The obtained results indicate that, similarly to traditional music instruments, the proposed digital musical instrument has a steep learning curve, and allows to produce expressive performances both from the performer and audience perspective.